A TAXONOMIC STUDY ON THE HEAD APPENDAGES ADULT BRUCHIDAE (COLEOPTERA) - SINGH, TARLOK (UTTAR PRADESH JOURNAL OF ZOOLOGY, 1986)
A taxonomic study on the head appendages of 39 species of Bruchidae has been made nae vary in size and shape and are 11-segmented with marked sexual dimorphism. The appearance, the shape of molar and incisor areas along with the presence or absence of cilia on the former are the mandibular characters for separating the sub-families. The has undivided cardo, stipes and galea; the setae on galea show variations at generic branched, simple, barbed and terminally bifid. The sclerotized stipital strips also variations at species level. The shape of the postmental sclerite and epilobes is import family level. However, the number of papillae considered on both the maxillary as well palps show specific variations.